ANALISA KEMANDIRIAN KEUANGA DAERAH KOTAMADYA METRO TAHUN 2009-2013 - Rita Rahmawati (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2016)
Giving local government to arrange regional receipt to purchase expenses bugget is part of Regional Otonomy. Not only depend on Central Government, Government genuine Receipt is one regional receipt that shows how stronger local goverment finance can handled all the expenditure. Metro as a local government in Indonesia, has the increase in regional otonomy espescialy in finance. The higher decentralization is a indicatoin that indicate higher ability on local government to fulfill all expenditure. It can be shown on share of Government Genuine Receipt and Tax and non Tax Share compare Total Regional Receipt and Total Regional Expenditure. Higher fiscal Desentralization needed by Metro to get higher Regional otonomy. Government Genuine Receipt and Tax and non Tax must be increased to get higher regional receipt and increasing share in Total Regional Receipt and higher share to offord the Total Regional Expenditure.